Antidepressant activities and regulative effects on serotonin transporter of Nardostachys jatamansi DC. (25th March 2021) - Li, Ran; Wang, Zhi-Mei; Wang, Yan; Dong, Xueqi; Zhang, Li-Hua; Wang, Tao; Zhu, Yan; Gao, Xiu-Mei; Wu, Hong-Hua; Xu, Yan-Tong
Abstract: Ethnopharmacological relevance: Nardostachys jatamansi (D.Don) DC. (family Caprifoliaceae, NJ) is well-documented and commonly used in the systems of traditional medicine in China, Tibet, Nepal, Bhutan, India and Japan for curing digestive and neuropsychiatric disorders with a long history of medication. However, the possible action mechanisms of antidepressant effects of NJ remain unraveled. Aim of the study: The aim of this study was to systematically investigate chemical substances of NJ and their effects on serotonin transporter (SERT) in antidepressant activity. Materials and methods: Antidepressant effects of total methanol extract of NJ were evaluated by tail suspension test (TST) and open field test (OFT). Then the total extract was analyzed by ultra-high-performance liquid chromatography (UHPLC) method, and its effect on SERT activity was evaluated by high content assay (HCA) to determine half maximal effective concentration (EC50 ). This total extract was subfractioned into twenty subfractions by preparative high-performance liquid chromatography ( p -HPLC) method, and 'subfraction-SERT activity' relationship curve was fitted with medians of the retention time of those subfractions and their SERT activity values. Then, the fraction NJFr.01 enriched with SERT enhancers was optimized, prepared and analyzed by UHPLC method. Antidepressant effects of the fraction NJFr.01 were evaluated by TST and OFT. Further, major constituents of the total extract and fraction NJFr.01 were isolated by p -HPLC and identified by extensive nuclear magnetic resonance (NMR) analyses and comparisons with those reported data, and their SERT activities were also evaluated. Finally, antagonistic effects of chlorogenic acid and desoxo-narchinol A against fluoxetine on SERT were evaluated. Results: Results of TST and OFT demonstrated antidepressant effects of toatal extract of NJ. The EC50 of total extract on SERT enhancement was 31.63 μ g/mL. The fitted 'subfraction-SERT activity' relationship curve revealed that fraction NJFr.01 was enriched with SERT enhancing constituents. Both total extract and fraction NJFr.01 significantly enhanced SERT activity, while the rest fraction NJFr.02 didn't show any SERT activity. Then, antidepressant effects of fraction NJFr.01 were demonstrated by TST and OFT. Further, phytochemistry investigation and UHPLC analyses confirmed the identification of fourteen constituents in the total extract of NJ, including 7-oxonardinoperoxide (1 ), desoxo-narchinol A (2 ), kanshone B (3 ), narchinol B (4 ), nardosinonediol (5 ), kanshone A (6 ), 1-hydroxylaristolone (7 ), debilon (8 ), nardosinone (9 ), kanshone H (10 ), 1, 8, 9, 10-tetradehydroaristolan-2-one (11 ), (−)-aristolone (12 ), 1(10)-aristolene-2-one (13 ) and jatamol A (14 ), and seven constituents in the fraction NJFr.01, including chlorogenic acid (15 ), 8 α -dihydrogeniposide (16 ), 7-deoxy-8- epi -loganic acid (17 ), adoxosidic acid (18 ), 8- epi -loganic acid (19 ), 8 α -6, 7-dihydroapodantheroside acetate (20 ) and 6″-acetylpatrinalloside (21 ). Their structures were established by NMR analyses and comparisons with those reported data. HCA results of these constituents demonstrated the major components of fraction NJFr.01 enhanced SERT activity. Antagonistic results showed that chlorogenic acid and desoxo-narchinol A reversed inhibition effect of fluoxetine on SERT activity. Conclusion: This study first systematically expatiated the roles of SERT activity in antidepressant effects of NJ, including total methanol extract and the water-soluble fraction NJFr.01 enriched with SERT enhancing constituents. This is the first report of natural SERT enhancing extract and fractions with antidepressant potential in NJ. Graphical abstract: Both total extract and fraction NJFr.01 of N. jatamansi possess antidepressant potentials.SERT Enhancers and inhibitors were co-existed in N. jatamansi .Antagonistic effects were observed between SERT enhancers of N. jatamansi and fluoxetine on SERT.Serotonin transporters play important roles in antidepressant effects of Nardostachys jatamansi DC. Image 1